Multipliers on Compact Lie Groups - Weiss, Norman J. (1971)
Sufficient conditions are found for a biinvariant operator on a compact Lie group to be bounded on L(p), 1 < p < ∞. The proof uses properties of g-functions on such a group, and an analog to the familiar relationship between differentiation and multiplication under the Fourier transform.